Sensitivity and specificity of pulp sensibility tests following traumatic dental injuries in permanent teeth: A one-year clinical study - Armita Rouhani; Hamed Karimi; Reza Shahmohammadi; Samuel Dorn; Hamid Jafarzadeh (Journal of Dental Materials and Techniques)
Objective: This study aimed to evaluate pulpal responses to sensibility tests after traumatic dental injuries and determine the sensitivity and specificity of these tests over time.Methods: Twenty-one patients with 51 traumatized teeth were included. After excluding 12 teeth during follow-ups, 39 teeth remained for final assessment. Pulp sensibility responses (electric pulp test (EPT), cold test, and heat test) were recorded at the initial visit and two weeks, one month, two months, and 12 months post-injury. The sensitivity and specificity of the tests were calculated using the response of traumatized teeth in the 12-month follow-up as the reference standard.Results: Lateral luxation was the most common injury. Among the 25 teeth with an initial negative response to sensibility tests, 4 concussions, 8 subluxations, 3 lateral luxation, 1 root fracture, and 1 uncomplicated crown fracture cases regained pulpal sensibility within one year. None of the immature teeth developed pulpal necrosis, whereas 7 out of 26 mature teeth did, primarily in lateral luxation cases. The specificity of the EPT increased from 0.47 on the first visit to 0.77 at two months and 0.83 at one year, with cold and heat tests showing similar trends. The sensitivity of cold and heat tests reached 1.0 at two months.Conclusions: Sensibility tests improved over time in traumatized teeth, with 17 out of 25 initially non-responsive teeth recovering within a year. No immature teeth developed necrosis. The specificity of all sensibility tests reached 0.83 in 12 months, and cold/heat test sensitivity reached 1.0 at two months.